2016
DOI: 10.5339/qmj.2016.16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of faith-based smoking cessation intervention during Ramadan among Malay smokers

Abstract: Objectives: To study the effects of a faith-based smoking cessation intervention during Ramadan among Malay male smokers working in public offices. Methods: This was a quasi-experimental study conducted during Ramadan 2015. The intervention was developed based on the constructs within the Theory of Planned Behaviour. The intervention intended to increase the intention and the perceived behaviour control to stop smoking among Muslim smokers during Ramadan. The outcomes measured were changes in the Fagerstrom Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…8,9 Islamic faith-based smoking cessation interventions have also been found to be effective in encouraging Muslim smokers to stop smoking during Ramadan, although the sustainability of the behavioural change is unclear. 12,39 Nevertheless, our findings are consistent with those from other studies targeting reduction of second-hand-smoke exposure within the home using behavioural interventions and indoor-airquality feedback. A review from 2018 found that the effectiveness of several counselling and educational interventions that have been used to try to reduce secondhand-smoke exposure has not been clearly shown.…”
Section: Discussionsupporting
confidence: 90%
“…8,9 Islamic faith-based smoking cessation interventions have also been found to be effective in encouraging Muslim smokers to stop smoking during Ramadan, although the sustainability of the behavioural change is unclear. 12,39 Nevertheless, our findings are consistent with those from other studies targeting reduction of second-hand-smoke exposure within the home using behavioural interventions and indoor-airquality feedback. A review from 2018 found that the effectiveness of several counselling and educational interventions that have been used to try to reduce secondhand-smoke exposure has not been clearly shown.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of tobacco control, our results raise issues for faith-based health interventions. Evidence primarily from the USA but also from the Far East and Muslim countries has been hopeful but equivocal about the effectiveness of such measures (Campbell et al 2007; Schoenberg et al 2016; Ismail et al 2016; Byron et al 2015; Elkalmi et al 2016). Our research points to the need for faith-based interventions to move beyond baseline prevalences to understand how religion interacts with other factors that may be more important in driving smoking behaviour, notably socio-economic disadvantage and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Research by [55] on the alternation of dietary and smoking patterns inspired by fasting during Ramadan found that consumption of tobacco products, tea, and coffee are markedly declined. Comparably, [55][56][57] observed a significant decline of 50% of the average number of cigarettes smoked, as well as higher rates of smoking cessation interventions during the month of Ramadan.…”
Section: Discussionmentioning
confidence: 93%